A plan to build a net zero energy building in hydrogen and electricity-based energy scenario in South Korea. (15th April 2023) - Jung, Yujun; Heo, Yeonsook; Cho, Honghyun; Kang, Yong Tae; Kim, Yongchan; Lee, Hoseong
Abstract: As net zero energy buildings (NZEBs) are attracting global attention, possible energy transition scenarios for NZEBs have been proposed in South Korea: (1) hydrogen-based or (2) electricity-based energy supply. Compared with a typical Korean residential building that uses a gas-fired boiler and air conditioner, the buildings in the two scenarios can significantly reduce energy consumption and emissions. In this context, this study aims to evaluate the performance of NZEBs in hydrogen- and electricity-based energy-supply scenarios based on simulation. An NZEB is constructed considering passive designs, active systems, and renewable energy systems. Subsequently, its performance is evaluated in terms of energy, environmental, and economic metrics, considering life cycle performance. The evaluation results confirm that the electricity-based energy scenario has better energy and environmental performance than the hydrogen-based energy scenario, with each scenario showing energy savings of 62% and 53%, respectively. In the electricity-based scenario, application of the passive design, active system, and renewable system accounts for savings of 48.2%, 21.2%, and 7.8%, respectively. Consequently, achieving NZEB requires more than 13 photovoltaic panels. In case of economic feasibility, all scenarios have positive operating cost savings. However, scenario 1 shows insufficient economic feasibility owing to high initial investment cost.